A Study on Agribusiness Management in Karnataka:A Case Analysis of Dry Chilies and its Products - K., Shivashankar; Banakar, Basavaraj (Indian Journal of Marketing, 2009)
The study was confined to north Karnataka with top two chilli growing districts viz., Haveri and Dharwad, which are represented a highest area under the chillies in Karnataka. Similarly, four important markets (Byadgi. Haveri, Kundagol and Hubli) were selected based on highest transactions and arrivals to the market of dry chillies in these districts. the results revealed that The per quintal cost of marketing incurred by the farmers in dry chilli in channel I was Rs.75.00 and in Channel II it was Rs 112.85/quintal.In the total marketing costs packing was the major component, which followed by sorting cost and transportation cost. These three components alone accounted for about 81.51 percent of the total marketing cost incurred by the farmers. On an average the producer's share in consumer's rupee in channel I was 77.74 per cent with a price spread of Rs 865.56/Quintal. Where I channel II an average producer share in consumer rupee was 78.46 percent which was found to be high as compared to channel-I. Retailer's share was higher in the total marketing margin as compared to other intermediaries in the chain. The magnitude of their share was much higher in the case of channel-II that is Rs 456.57/quintal when compared to the channel-I Rs 356.56/quintal.